A thematic study of creativity research in Spain within the social sciences and psychology - De-Marchis, Giorgio; Shchebetenko, Sergei (Anales de Psicología / Annals of Psychology, 2023)
Creativity is becoming one necessary human skill in a world where robots increasingly outperform people in daily routines. In order to efficiently develop creativity as a research field, scholars need to know where they are. We employed a bibliometric approach to study themes and characteristics of creativity research in Spain. The results indicated that publication production in the field has been growing during the last decades. Compared to psychology, creativity in the social sciences seemed to be an undercited, local, and endogamic area. For social sciences, motor themes in the last decade were a) creativity in children and students in the educational environment, b) innovation and knowledge creation in a working environment, and c) cities and creativity. The motor themes in psychology were a) individual characteristics for generating insights (e.g., skills, improvisation, executive functions) and b) emotional intelligence. We suggest some themes for future research, such as creative collaboration in virtual environments, value co-creation, and how machines can help humans boost their creativity.